Groundwater Conditions and Hydrogeochemistry of the Sombreiro-Warri Deltaic Plain Deposit (Shallow Benin Formation) in the Vicinity of Agbarho, Nigeria - Efobo, O.; Ugbe, F. C.; Akpoborie, I. A. (Journal of Scientific Research, 2020)
Groundwater conditions and hydrogeochemistry in the Sombreiro-Warri Deltaic Plain deposit at the Agbarho area were described with the aid of data obtained from dug wells. Ten dug wells and two surface water locations were sampled for water quality analysis. Regional groundwater flow is from the northeast to southwest direction with local distortion resulting from sustained groundwater withdrawal in more populated areas of the town. pH in surface water range was from 4.9 to 5.4 and that of groundwater from 3.8 to 5.9. TDS in groundwater and surface water ranges were from 39.6 to 123 mg/L and 9 to 25.6 mg/L, respectively. Two hydrochemical facies, magnesium chloride and sodium chloride facies were defined in this study. The order of abundance of cations are Mg>Na+K>Ca, Na+K>Mg>Ca and Na+K>Ca>Mg and for anions is Cl>HCO3>SO4. This study indicates that the groundwater chemistry is controlled largely by precipitation. Water qualities from the dug wells and surface water are well within the SON permitted levels except faecal coliform occurring at minimal level in two wells and one of the locations on the river.